METHYL GREEN-PYRONIN : I. BASIS OF SELECTIVE STAINING OF NUCLEIC ACIDS - Kurnick, N. B. (The Rockefeller University Press, 1950)
1. Methyl green stains selectively highly polymerized desoxyribonucleic acid, and fails to stain, to any significant extent, depolymerized desoxyribonucleic acid and ribonucleic acid. 2. Pyronin stains preferentially low polymers of nucleic acid. 3. Triphenylmethane dyes with two amino groups appear to share the selectivity of methyl green. Those with three amino groups are not selective. 4. A stereochemical hypothesis is offered to account for these observations.